Detection and Measurement of Stones With Ultrasound Strain Elastography: A Phantom Study. Issue 4 (December 2015) - Li, Qian; Chen, Lei; Halpern, Elkan F.; Samir, Anthony E.
Abstract : Abstract: The sonoelastographic appearances of stones in a phantom were evaluated in this study. Ten stones were embedded into a tissue-mimicking meat phantom. The stone axial (vertical) and transverse (horizontal) dimensions measured by an electronic digital caliper, gray-scale ultrasound, and strain elastography (SE) were compared in 5 groups with stones embedded at different depths. In this study, physically measured axial and transverse stone dimensions were 1.17 to 6.86 and 1.30 to 11.15 mm, respectively. Strain elastography showed a characteristic 3-layer pattern associated with stones, comprising a superficial transition region, a hard region, and a deep transition region. As SE data were available in group 5, only data of groups 1 to 4 were analyzed. Compared with physical measurements, measurement mean errors of SE horizontal and SE vertical dimensions ranged from −0.20 to 0.42 mm and from −1.28 to −0.05 mm, respectively, in the 4 groups. Paired t testing demonstrated a significant horizontal dimension measurement error difference between B mode and SE method in group 4 (0.44 vs −0.20 mm, P < 0.05; F = 1.18, P > 0.05), but not in the other groups. Strain elastography horizontal dimension measurement error was not statistically correlated with stone size in the 4 groups. Strain elastography vertical dimension measurement error significantly correlated with stone size only in group 4 ( P < 0.05). Preliminary results indicate that stone horizontal and vertical dimensions can be measured using SE in a soft tissue phantom, including when shadowing precludes measurement of vertical dimension on conventional 2-dimensional ultrasound. These results provide substantial motivation to further investigate SE as a modality to image stones in clinical practice.